Superação da dormência de sementes e controle químico de cordas-de-viola (ipomoea spp.) em soja resistente ao glifosato - Pinheiro, Rodrigo Trindade (2010)
Morningglory is an annual plant reproduced by seeds. Seed germination occurs in streams during spring and summer making it difficult to control. Its occurrence has increased in soybean crops in southern states by the exclusive use of the herbicide glyphosate in weed control. This species has seed dormancy caused by impermeable to water, whose absorption is prevented by the seminal tegument. The possibility of using effective methods to overcome dormancy of seeds of bindweed would be ideal for studies of management of these species in agroecosystems as this would result in more uniform plant stands. This study aimed to: evaluate methods aimed at breaking dormancy of seeds of three species of morningglory, and investigate whether there are differences in dormancy between species of this weed (Chapter I); select alternative techniques in weed management prior to sowing of soybean by desiccation with glyphosate, alone and in combination with residual herbicides and selective culture, and also in post -emergency soybeans, with or without the application of glyphosate (Chapter II). In the experiment of scarification, sulfuric acid treatment (98%) resulted in increases in germination varies according to the species examined. Ipomoea undivided was less sensitive to treatment, for Ipomoea triloba, soaking the seeds for 10min in H2SO4 showed better germination. Already in Ipomoea purpurea, the response was linear and the best germination of this species occurred in time of 20min. Mechanical scarification enhanced germination of three species, because it promotes a break in the integument allowing more water uptake by seed. Soaking in KNO3 (0.2% v/v) promoted germination below 40% for the three species to morningglory. Seed exposure to radiation Ipomoea triloba ultrasound for 45 and 60 min resulted in germination percentage above 70%, but for Ipomoea purpurea and Ipomoea indivisa germination was below 50%. The results of experiment management of morningglory showed that the treatments applied in the pre-drying in soybean planting this species is not adequately controlled, controlling less than 80%. But the assessment at 14 DAT, treatments T3 (glyphosate + diclosulam) and T2 (glyphosate + clorimuron) controlled respectively 88 and 86%. In general, the highest grain yields were obtained when combining the treatments of drying with application of glyphosate V2 and V5 stages of soybeans, or just in V5, except for T1 (glyphosate - 720) and T4 (glyphosate + imazethapyr - 720 + 90). T3 (glyphosate + diclosulam - 720 + 25.2) stood out positively desiccation on pre-seeding, controlling the flow of seedling emergence in morningglory (81% at 28 DAT) and also in productivity grains (3.116 kg ha-1) when it was applied post-emergence glyphosate in soybeans. The application of the herbicide glyphosate has shown effective results in the management of morningglory. Therefore, it is necessary the use of combined applications of herbicides. The integrated management of weeds must not dismiss the use of herbicides, but control of the morningglory in soybean requires a management that includes addition of chemical control, several cultural practices, and therefore will require more investment by the producer but to have a greater return due to increased profitability.